An enhanced and secure trust‐extended authentication mechanism for vehicular ad‐hoc networks. Issue 17 (25th August 2016) - Kumari, Saru; Karuppiah, Marimuthu; Li, Xiong; Wu, Fan; Das, Ashok Kumar; Odelu, Vanga
Abstract: Vehicular Ad‐hoc Networks (VANETs) are a move towards regulating safe traffic and intelligent transportation system. A VANETs is characterized by extremely dynamic topographical conditions owing to speedily moving vehicles. In VANETs, vehicles can transmit messages within a pre‐defined area to achieve safety and efficiency of the system. Then ensuring authenticity of origin of messages to the receiver in such a dynamic environment is a crucial challenge. Another concern in VANET is preservation of privacy of user/vehicle. Recently, Chuang and Lee proposed a trust‐extended authentication mechanism (TEAM) for vehicle‐to‐vehicle communications in VANETs. TEAM not only satisfies various security features but also enhances the performance of the authentication process using transitive trust relationship among vehicles. Nonetheless, our analysis shows that TEAM is vulnerable to insider attack, privacy breach, impersonation attacks and some other problems. In this paper, to eradicate the vulnerabilities found in Chuang‐Lee's scheme, an enhanced trust‐extended authentication scheme for VANET is proposed. We display the efficiency of our scheme through security analysis and comparison. Through simulation results using widely accepted NS‐2 simulator, we show that our scheme authenticates vehicles faster than Chuang‐Lee's scheme. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : We examine recently proposed Chuang and Lee's scheme for Vehicular Ad‐hoc Networks for its security weaknesses. We propose an improved scheme for Vehicular Ad‐hoc Networks. We display the efficiency of our scheme through security analysis, NS‐2 simulation and comparison.